2012
DOI: 10.1002/ccd.24421
|View full text |Cite
|
Sign up to set email alerts
|

The science behind percutaneous hemodynamic support: A review and comparison of support strategies

Abstract: Patients in a variety of cardiovascular disease states may benefit from temporary percutaneous cardiac support, including those in acute decompensated heart failure, fulminant myocarditis, acute myocardial infarction with or without cardiogenic shock and those undergoing high-risk percutaneous coronary intervention. The ideal percutaneous cardiac support device is safe, easy to use and versatile enough to meet the needs of various clinical situations and patient cohorts. In addition, it should provide maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 47 publications
1
71
0
1
Order By: Relevance
“…These differences influence overall haemodynamic effects and the degree of ventricular unloading (Figure 1). 1 The latter has a substantial effect on myocardial oxygen demand, which has been shown to influence infarct size and long-term ventricular function in animal models. The expanded use of extracorporeal membrane oxygenation for cardiogenic shock (excluded from these previous utilization studies) raises other questions, not only associated with its very different haemodynamic effects, but also because of its effects on blood components and systemic inflammation.…”
Section: News and Viewsmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences influence overall haemodynamic effects and the degree of ventricular unloading (Figure 1). 1 The latter has a substantial effect on myocardial oxygen demand, which has been shown to influence infarct size and long-term ventricular function in animal models. The expanded use of extracorporeal membrane oxygenation for cardiogenic shock (excluded from these previous utilization studies) raises other questions, not only associated with its very different haemodynamic effects, but also because of its effects on blood components and systemic inflammation.…”
Section: News and Viewsmentioning
confidence: 99%
“…Such devices include intra-aortic balloon pumps (IABPs), extracorporeal blood pumps, and catheter-based miniature blood pumps. 1 These devices are collectively referred to as percutaneous ventricular assist devices (pVADs). Until around 2014, IABPs were a mainstay of therapy for cardiogenic shock.…”
mentioning
confidence: 99%
“…Ultimately, the goal of MCS is to improve hemodynamics by augmenting or providing full cardiac output, producing a physiologically acceptable blood pressure and reducing pulmonary venous pressure when traditional pharmacological therapies are inadequate. Alternatively, MCS is also used prophylactically in high risk procedures for expected and transient impairment in the cardiovascular hemodynamics (2). Achieving these goals results in improved end-organ perfusion and, in cases of volume overload states, improved diuresis.…”
Section: Advanced Hemodynamicsmentioning
confidence: 99%
“…While these factors are considered when deciding which MCS devices to utilize, these differences are only partially understood and have not been fully researched in clinical trials (2). Ultimately, the goal of MCS is to improve hemodynamics by augmenting or providing full cardiac output, producing a physiologically acceptable blood pressure and reducing pulmonary venous pressure when traditional pharmacological therapies are inadequate.…”
Section: Advanced Hemodynamicsmentioning
confidence: 99%
“…Specifically, the Impella 5.0 offers full systemic circulatory support (up to 5 L/min), direct LV unloading, and minimally invasive implantation without sternotomy. 12 An increase in patient survival, an increase in cardiac output, and a reduction in the use of inotropes and vasopressors as early as 24 hours after intervention were demonstrated by the Detroit Cardiogenic Shock Initiative using early implantation of the Impella device in patients with acute MI and cardiogenic shock. 13 Moreover, Remmelink et al, in a small cohort of MI patients, showed the benefit of LV unloading by a decrease in end-diastolic LV wall stress.…”
mentioning
confidence: 99%